2009
DOI: 10.3177/jnsv.55.106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Resistance Exercise after Ingestion of a High-Protein Snack on Plasma Branched-Chain Amino Acid Concentrations in Young Adult Females

Abstract: SummaryWe have previously reported the preventive effects of light resistance exercise (voluntary tower climbing exercise) after ingestion of a high-protein snack (HPS) on muscle loss in glucocorticoid-injected rats. However, such studies have not been performed in humans. In this cross-over study, we examined the effect of light resistance exercise after ingestion of HPS on plasma branched-chain amino acid (BCAA) concentrations in humans. Seven healthy young adult females (aged 22.1 Ϯ 1.2 y) participated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, it is difficult for the elderly to continue heavyload exercise on a daily basis. Recent studies have reported that even light resistance exercise such as lowspeed muscle flexing and extending exercise (10), is effective in increasing muscle mass and strength by restricting blood flow (9): this study used a dumbbell exercise devised by Suzuki that can be practiced even by the elderly (3,5,6). Movements in this exercise are very slow, with the subject's muscle blood flow being restricted by holding the light dumbbells (300 g) and adducting the wrists, which promotes protein synthesis and excretion of growth hormones (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult for the elderly to continue heavyload exercise on a daily basis. Recent studies have reported that even light resistance exercise such as lowspeed muscle flexing and extending exercise (10), is effective in increasing muscle mass and strength by restricting blood flow (9): this study used a dumbbell exercise devised by Suzuki that can be practiced even by the elderly (3,5,6). Movements in this exercise are very slow, with the subject's muscle blood flow being restricted by holding the light dumbbells (300 g) and adducting the wrists, which promotes protein synthesis and excretion of growth hormones (11).…”
Section: Discussionmentioning
confidence: 99%
“…Further, to determine whether the above effect could be observed in humans, we investigated changes in plasma branched-chain amino acid (BCAA) concentrations to determine whether light resistance exercise (dumbbell exercise) performed with high plasma BCAA concentrations resulting from ingestion of HPS 3 h after a basal meal is effective in the promotion of amino acid utilization by peripheral tissues ( 3 ). HPS ingested 3 h after a basal meal increased the plasma BCAA concentrations.…”
mentioning
confidence: 99%
“…It is thought that the climbing exercise in rats also causes intermittent blood volume fluctuation in muscle tissues, similar to that which arises during dumbbell exercise in human subjects ( 4 ).…”
mentioning
confidence: 99%
“…Performing dumbbell exercise in half-crouching position, with the upper body angled forwards, grasping the dumbbells firmly, twisting the wrists inward, and keeping them curled ( 5 , 6 ) resulted in reduced blood volume in the antebrachial and femoral muscles during exercise and sudden increase in blood volume during the interval period between exercise sets ( 4 ). It is thought that the climbing exercise in rats also causes intermittent blood volume fluctuation in muscle tissues, similar to that which arises during dumbbell exercise in human subjects ( 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation